Solvatochromism of Dyes Inspired in Effenberger S Probe - Caroli-Rezende, M; Dominguez-Caru, M (Elsevier Ltd, 2021)
Solvatochromic dyes have been utilized in recent decades as probes to measure the polarity of the medium. An interesting example is the Effenberger s dye (ED), which exhibits a very pronounced positive solvatochromism, being considered a dye that probes practically only the polarizability and dipolarity of the medium. This compound is difficult to be accessed and, in addition, the synthesis of dyes capable to probe the polarizability of the medium is a subject of interest. In view of this, six imine probes inspired in the molecular structure of ED were synthesized and characterized. Two compounds were solvatochromic and exhibit different colors in various solvents, while the other dyes exhibit a weak solvatochromism. Three probes present a behavior very similar to ED, showing a positive solvatochromic behavior. The application of multiparametric equations shows that polarizability is the most influential solvent parameter in the solvation of the dyes studied. Theoretical calculations were performed with a dye in ten different solvents, employing a continuum model to mimic solvent effects and TD/DFT calculations with two functionals exhibiting a different degree of Hartree–Fock exchange to estimate transition energy (ET) values. A HOMO–LUMO transition involving an internal charge transfer from the N,N–dimethylaminophenyl electron–donor to the nitrothienyl electron–acceptor moieties of the dye was identified as the origin of the solvatochromic band. The calculated ET values reproduce qualitatively the positive solvatochromism of the dye. The results obtained show that the easy synthesis of solvatochromic compounds, inspired in the ED, represents an interesting possibility in the research for novel polarizability probes. © 2020 Elsevier Ltd